Método Ballester na alfabetização: análise de uma proposta didática contextualizada pelas ciências da natureza - Moura, Marcelo Bueno (2025)
Literacy is a crucial stage in children's educational development, but traditional methods are not always effective in promoting meaningful learning. The challenge is to develop approaches that foster meaningful learning throughout the literacy process. In the contemporary educational landscape, the Ballester Method emerges as an innovative approach to promoting meaningful learning in the early years of elementary school. Based on the principles of Theory of Meaningful Learning, this method aims to actively engage students in their learning process, connecting new knowledge with their previous experiences. However, its application in children's literacy presents specific challenges, requiring adaptations to make the content accessible and relevant to children in this age group. Therefore, the question is: What are the potential contributions of the Ballester Method to the literacy process, with Natural Sciences as a contextualizing theme? The objective of this research is to evaluate a teaching proposal aimed at teaching literacy to first-grade elementary school students, supported by the Ballester Method, with the Natural Sciences as its contextualizing theme. The frameworks, supported by discussions on literacy and literacy, meaningful learning, the Ballester Method, and contextualization through the Natural Sciences, supported the development of a teaching proposal in the form of a Didactic Activity Booklet, considered an educational product associated with the thesis. The activities, structured by the key variables outlined in the Ballester Method, are implemented in 24 two-hour meetings in a first-grade elementary school class at a public school in Goiás. This qualitative, action-research study uses three data collection instruments: a logbook completed by the researcher; material produced by the students during the activities; and video recordings used to extract information about the activities. The results, organized into teaching episodes according to the chosen analytical strategy, indicate that the Ballester Method is viable for literacy, as it promotes engagement, authorship, and systematization of knowledge, reinforcing the importance of integrating literacy and literacy, avoiding instrumental reductionism. Furthermore, the study contributes to the field of literacy and studies involving the application of the Ballester Method by documenting its application in the early years, an area still little explored. It also provides an opportunity for the production of pedagogical material in the form of an educational product, ready for use and adaptation by teachers. Literacy can be qualified when it is supported by methodologies that do not merely teach reading and writing, but rather make sense for students, valuing their prior knowledge and bringing them closer to social and scientific reality. The Ballester Method to be articulated in Nature Sciences, shows a promising alternative to return to literacy, reaffirming that literacy is also teaching the world. The study demonstrates the feasibility and effectiveness of the Ballester Method in literacy, favoring engajamento, authoría and systematicação do conhecimento. The educational product, entitled "Workbook of Didactic Activities for Literacy Based on the Ballester Method and in Dialogue with the Natural Sciences," is available at: http://educapes.capes.gov.br/handle/capes/1133456.